2012
DOI: 10.1590/s0100-736x2012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação espontânea por Sorghum sudanense em bovinos leiteiros no Rio Grande do Sul

Abstract: Pesq. Vet. Bras. 32(3):217-220, março 2012 217 RESUMO.-Descreve-se um surto de intoxicação espontâ-nea por Sorghum sudanense (aveia de verão, capim-sudão) em um rebanho de bovinos leiteiros no município de Triunfo, Rio Grande do Sul. Essa planta é utilizada como forrageira em diversas regiões do estado; entretanto, intoxicações ocasionais são associadas com a formação de ácido cianí-drico por hidrólise dos glicosídeos cianogênicos presentes na planta. Vinte e nove vacas Holandesas foram colocadas, no ϐinal do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
3
0
5
Order By: Relevance
“…The clinical-pathological condition observed in spontaneous poisoning by star grass Florico cultivar is in agreement with that described by other authors for cyanogenic plants (Saad & Camargo 1967, Canella et al 1968, Kellerman et al 1988, Gava et al 1992, Tokarnia et al 1994a, 1994b, 1999, Gava et al 1997, Radostits et al 2002, Youssef & Maxie 2004, Amorim et al 2005, Nóbrega Junior et al 2006, Riet-Correa & Méndez 2007, Oliveira et al 2008, Carvalho et al 2011, Juffo et al 2012, Galindo et al 2017.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The clinical-pathological condition observed in spontaneous poisoning by star grass Florico cultivar is in agreement with that described by other authors for cyanogenic plants (Saad & Camargo 1967, Canella et al 1968, Kellerman et al 1988, Gava et al 1992, Tokarnia et al 1994a, 1994b, 1999, Gava et al 1997, Radostits et al 2002, Youssef & Maxie 2004, Amorim et al 2005, Nóbrega Junior et al 2006, Riet-Correa & Méndez 2007, Oliveira et al 2008, Carvalho et al 2011, Juffo et al 2012, Galindo et al 2017.…”
Section: Discussionsupporting
confidence: 89%
“…Arg. (Amorim et al 2005), Manihot piauhyensis (Canella et al 1968), Sorghum sudanense (Juffo et al 2012), Sorghum halepense (Nobrega Junior et al 2006), Passiflora foetida (Carvalho et al 2011), Piptadenia macrocarpa (Tokarnia et al 1994b), Piptadenia viridiflora (Tokarnia et al 1999), Prunus sphaerocarpa (Saad & Camargo 1967), Prunus sellowii (Gava et al 1992) and Tifton 68 (Gava et al 1997, Galindo et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…"Florico" was marked by the rapid (5-15 min) appearance of muscle tremors, dyspnea, ruminal atony, bloat, wobbling, frequent and/or dripping urination, tachycardia, depression, ocular mucous membranes and venous blood of a bright red color, and sternal or lateral recumbency. This clinical condition is similar to that described in relation to cyanogenic plants by other authors (Saad & Camargo 1967, Canella et al 1968, Kellerman et al 1988, Gava et al 1992, Tokarnia et al 1994a, 1994b, 1999, Gava et al 1997, Radostits et al 2002, Youssef & Maxie 2004, Amorim et al 2005, Nóbrega Junior et al 2006, Riet-Correa & Mendez 2007, Oliveira et al 2008, Carvalho et al 2011, Juffo et al 2012, Galindo et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…It is suggested that the incidence of hepatic necrosis of sheep fed control diet may have been caused by the presence of other antinutritional factors in this plant, such as HCN. Juffo et al (2012) observed that Tifton-grass (Cynodon dactylon) is a species involved in HCN poisoning. The necrosis of hepatocytes is probably due to the low oxygenation caused by HCN, which has an affinity of iron, decreasing the availability to binding oxygen in erythrocytes, breaking the respiratory chain, and causing histotoxic anoxia (Rufino, 2014).…”
Section: Resultsmentioning
confidence: 99%